Acceleration of spontaneous visual recovery by voluntary physical exercise in adolescent amblyopic rats - Di Marco, Irene; Sansevero, Gabriele; Berardi, Nicoletta; Sale, Alessandro (Frontiers in Cellular Neuroscience, 2024)
Abnormal visual experience during development resulting from an imbalance in the activity of the two eyes can lead to permanent severe visual deficits, a pathology called amblyopia (lazy eye). While this condition is extremely difficult to treat in adults, current interventions can elicit significant amounts of visual recovery when performed in juveniles before the end of the critical period, even if the achievable results can be unsatisfactory due to the progressive decline in visual cortical plasticity. Similarly to human subjects, rodents becoming amblyopic due to early visual deprivation can display spontaneous functional recovery if the deprivation ends within the critical period time window. With the aim to investigate the impact of non-invasive strategies able to increase this spontaneous potential for plasticity, we wondered whether physical exercise could speed up spontaneous recovery of visual functions in juvenile amblyopic rats. Our results show that physical exercise accelerates visual recovery in adolescent rats, encouraging application of behavioral plasticizing treatments to promote recovery in young individuals.